Prevalence Of The Ppargc1a Gene Gly482ser Polymorphism In Women With Obesity (Texas Journal of Medical Science, 2026)
In recent years, according to leading scientists, a hereditary predisposition to obesity has been identified. Various mutations that significantly affect energy metabolism and adipose tissue proliferation can lead to the development of obesity, but in most patients they are not detected. This article presents the results of research on proving the prevalence of the PPARGC1A gene polymorphism in Uzbek women of childbearing age with obesity and creating the necessary conditions for determining the potential goals of drug therapy and developing personalized effective approaches to the diagnosis, treatment, and prevention of obesity.